KOSAKATA MERATEH DALAM BAHASA MELAYU DIALEK SAMBAS - Septiani, Dea; Patriantoro, Patriantoro; Jupitasari, Mellisa; Simanjuntak, Hotma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to find out and describe the vocabulary of merateh in the Sambas dialect of Malay. This research is qualitative with a descriptive method. The data collection techniques used include observation techniques and interview techniques. Data collection tools, namely researchers as key instruments and assisted by other equipment such as observation lists, question lists, notebooks, stationery, and gadgets. The source of data for this research is an informant who speaks Malay in the Sambas dialect. The data of this study are all vocabulary of the Sambas dialect of Malay. The results of the study showed that 98 vocabulary words were found in the form of lingual units consisting of monomorphic forms totaling 26 words, polymorphic forms of affixation parts amounting to 40 words, polymorphic forms of reduplication parts amounting to 5 words, and phrases amounting to 27 words. The results of the data of 98 vocabulary words were analyzed based on the type of meaning contained in merateh had 98 lexical meanings and 70 grammatical meanings.